Thromboangiitis obliterans (Buerger's disease) - a review - Bogacz, Rafał; Gaik, Magdalena; Uram, Ewa; Magda, Inga; Woźniak, Justyna; Womperski, Karol; Osuch, Magdalena (Journal of Education, Health and Sport, 2023)
Introduction: Thromboangiitis obliterans (Buerger's disease) is a segmental, multilocular, nonatherosclerotic inflammatory disease that most commonly affects small and medium sized arteries, veins and nerves of the extremities. The disease is spread worldwide and mainly affects young male tobacco smokers. Aim of study: In this review we gather and summarize available knowledge about pathogenesis, diagnosis and methods of treatment of Thromboangiitis obliterans. Methods and materials: Search of the articles in PubMed and GoogleScholar databases was performed using following keywords: Thromboangitis obliterans; Buerger's disease; Thromboangitis Obliterans pathogenesis; Thromboangitis Obliterans diagnosis; Thromboangitis Obliterans treatment; Thromboangitis Obliterans pathophysiology; Thromboangitis Obliterans symptoms; Thromboangitis Obliterans epidemiology; Thromboangitis Obliterans risk factors; The most relevant to the topic articles were included. Summary: Even though the causes of the disease remain unclear and treatment is still difficult, there are new experimental methods of treatment being researched that may bring a breakthrough in the future.